Pomiędzy dewocją, polityką i sztuką. Symbolizm historyczny w malarstwie książkowym w kręgu dworu burgundzkiego w Niderlandach (ok. 1455-1482) = - Płonka-Bałus, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the light of research concerning the history of art, the assumption on the regress of the 15th century historic idea, manifesting itself in the transformation of historiography into ?knightly chronicles? stands out against its power of influence in other fields of culture. Affluent historic literature, close to the poetry of chanson de geste, became the field of activity of various eminent masters of book painting, particularly active in the area of France as well as the Duchy of Burgundy ? culturally and territorially close to France. The fascination with antiquity cultivated in the circles of elites of that times (particularly with the figure of Alexander the Great) was accompanied with the interest in the knight culture and the deeds by local epic heroes (Girart de Roussilon), direct predecessors or the idea antecedents of founders of the 15th century?s editions of their history, were consciously included in the process of power legitimization.
Keywords: symbolizm; malarstwo książkowe; Niderlandy; 15 w.